Synthesis of some 5-substituted-1,2,4-triazole-3-thiones, containing thiourea, arylidenamino and morpholin-4-yl methyl fragments - Koparir, Metin; Koparir, Pelin; Cansiz, Ahmet; Temuz, Mehmet Mursit (Chemical Publishing Co., 2010)
In this study, first 4-amino-5-(pyridine-4yl)-4H-1,2,4-triazole-3- thione (1) and 4-amino-5-(2-hydroxyphenyl)-4H-1,2,4-triazole-3-thione (2) were synthesized. In the second step (1) and (2) compounds undergo reaction with aryl isothiocyanates in dry C6H6 to give corresponding N-substituted thiourea derivatives (3a-d and 4a-d). In addition, in the another reaction (1) and (2) compounds were reacted with some aromatic aldehyde in anhydrous ethanol to give corresponding arylidenamino compounds (5a-d and 6a-d). In the third step, aminomethylation derivatives (7a-d and 8a-d) were obtained by the Mannich reactions of arylidenamino compounds (5a-d and 6a-d), with formaldehyde/ morpholine in ethanol. The structures of all the synthesized compounds were confirmed by elemental analyses, FT-IR, 1H and 13C NMR spectra.
Keywords: 1,2,4-Triazole; Arylidenamino; Mannich bases; Thiourea